الأسس الربانية في تعليم العلوم الكونية الحديثة عند سعيد النورسي - Muhammad Widus Sempo; Haniah Mukhtar; Mahyuddin Hashim; Mohammed Akhiruddin Ibrahim (Universiti Sains Islam Malaysia, 2024)
In order to revive the glory of Islamic civilization, there are many holistic approaches, traditionally dated from the 8th to the 15th century. However, the challenge facing all people is the scientific dichotomy between science and the religious sciences in the national education system. Most scholars of Islamic education realize that there is no other way to reach back this glory except by reviving the integrative education which combines science-technology and religion. Said Nursi is one of the most prominent scholars of the 20th century who highlighted the importance of having a properly educational approach that embraced together religious sciences (Shari'a) and modern sciences. Therefore, it is necessary to examine the 'Risale-I Nur' with further employment of analytical approach to its text. The aim is to draw attention to the divine foundations that Nursi views as the principle and starting point of the divine method in teaching of modern science. The study showed that Nursi saw both Sharia and modern cosmological sciences require each other, without any refrainment from both sides. This is because God Almighty had beautiful names and attributes, and the discoveries of modern science reveal these names and attributes very clearly, which is the purpose for the Shari'a given to the master of mankind, Muhammad (peace be upon him).